2001
DOI: 10.1038/sj.cr.7290083
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin II type 1 receptor and receptor-associated proteins

Abstract: The mechanisms of regulation, activation and signal transduction of the angiotensin II (Ang II) type 1 (AT1) receptor have been studied extensively in the decade after its cloning. The AT1 receptor is a major component of the renin-angiotensin system (RAS). It mediates the classical biological actions of Ang II. Among the structures required for regulation and activation of the receptor, its carboxyl-terminal region plays crucial roles in receptor internalization, desensitization and phosphorylation. The mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
126
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(135 citation statements)
references
References 113 publications
1
126
1
7
Order By: Relevance
“…3, B and C). It has been reported that a general acceleration of cellular endocytic pathways and agonist-induced endocytosis of some receptors (such as the angiotensin II receptor) does not affect the production of A␤ and ␥-secretase activity (49,50). Thus, internalization of PS-1 (␥-secretase) with the EP 4 receptor seems to enhance production of A␤ and ␥-secretase activity specifically.…”
Section: Contribution Of Co-internalization Of Ps-1 With the Ep 4 Recmentioning
confidence: 99%
“…3, B and C). It has been reported that a general acceleration of cellular endocytic pathways and agonist-induced endocytosis of some receptors (such as the angiotensin II receptor) does not affect the production of A␤ and ␥-secretase activity (49,50). Thus, internalization of PS-1 (␥-secretase) with the EP 4 receptor seems to enhance production of A␤ and ␥-secretase activity specifically.…”
Section: Contribution Of Co-internalization Of Ps-1 With the Ep 4 Recmentioning
confidence: 99%
“…In some cases, however, Ca 2+ and PKC are involved. 18 Since it is known that high enough intracellular calcium can uncouple gap junction channels 19 and that Ang II increases Ca 2+ i, 9 an additional mechanism for the action of losartan might be a possible decrease of the intracellular calcium concentration.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
“…Angiotensin II (Ang II) is a pleiotropic vasoactive peptide that binds to two specific receptor subtypes, AT 1 and AT 2 (7,8). Only a single AT 1 receptor gene is present in humans, but this receptor is encoded by at least two distinct genes (AT 1a and AT 1b ) in rodents, with 96% homology (9). AT 1 contributes to chronic diseases, such as hypertension, renal injury, atherosclerosis, and cardiac hypertrophy, by promoting cell growth, in-flammatory responses, and fibrosis.…”
mentioning
confidence: 99%
“…The Ang II signal transduction is mediated by G proteins, which activate several intracellular pathways, including Ca 2ϩ / protein kinase C (PKC), mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase, and numerous tyrosine kinases, such as Src, Pyk2, p130Cas, and focal adhesion kinase (9,10). Ang II also activates nuclear transcription factors, including NF-B, activating protein-1, cyclic adenosine monophosphate response element binding protein, and nuclear factor of activated T cells (12,13,14).…”
mentioning
confidence: 99%